Kebijakan Pengembangan Ilmu di Universiti Islam Antarabangsa Malaysia - Syamsul Huda (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2015)
The concept of policy developing knowledge both at IIUM integrates the knowledge into religious knowledge (fardhu ayn) and science(fardu kifayah) by using the concept of Imam al-Ghazali (ihya’ulum al-din). Both IIUM develop religious knowledge to all of their students, and develop science to a part of students based on their choices and departments though education, research and dedication to society. IIUM integrates the development of knowledge either fardu ayn orfardu kifayah only in the units, faculties, and departments not on-Campus Housing. Furthermore, on-Campus Housing at IIUM is not functioned as a place to develop intellectuality, akhlaq and spirituality, but merely as facilities (mushalla, imam/leader of communal prayer and weekly discussion) eventough the student study here for four years (S1).